CD73-Positive Small Extracellular Vesicles Derived From Umbilical Cord Mesenchymal Stem Cells Promote the Proliferation and Migration of Pediatric Urethral Smooth Muscle Cells Through Adenosine Pathway - Zhang, Shilin; Li, Jierong; Li, Chunjing; Xie, Xumin; He, Jun; Ling, Fengsheng; Li, Bowei; Wu, Huayan; Li, Zhilin; Zheng, Jianwei (Frontiers in Bioengineering and Biotechnology, 2022)
Graphical Abstract Graphical diagram of CD73/Adenosine/PI3K/AKT axis in facilitating cell proliferation and migration of PUSMCs in vitro.